Prevalence of Uterus Prolapse in Pregnant Females of Lahore: A Cross-sectional Survey - Asma, Shafaq; Naseer, Amna; Ashraf, Hafiza Sana; Sohail, Maria; Asif, Tooba; Safdar, Zainab (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2020)
Uterus prolapse is a common gynecological condition which is relatively less common during pregnancy. Prolapse maybe conceptualized as a type of herniation or bulge of the pelvic organs into or out of the vagina because of damage or weakness of connective tissues and muscles of pelvic floor area Objective: The objective was to determine the prevalence of uterus prolapse among pregnant females. Methods: This cross-sectional study was conducted in pregnant females. Sample size of 189 was calculated. Standardized questionnaire was used for data collection Results: A bulge or protrusion falling out that you can see or feel in your vagina was moderately present in 5.3% (10) females. Heaviness in the pelvic area was felt by 6.9% (13) females. Along with prolapse there was weakness in pelvic floor muscles and ligaments so that the leakage of urine is present in 3.7% (7) females Conclusions: Uterus prolapse is mildly present in 8.5% and moderately present among 5.3% of pregnant females varying with their age, parity and strength of pelvic floor structures. All females with prolapse have a bulge in their vagina but its severity is different in every woman.